Mechanisms of allergen-specific immunotherapy: Multiple suppressor factors at work in immune tolerance to allergens - Akdis, Mübeccel; Akdis, Cezmi A. (Journal of allergy and clinical immunology, 2014)
Allergen-specific immunotherapy (AIT) has been used for more than 100 years as a desensitizing therapy for IgE-mediated allergic diseases and represents a potentially curative way of treatment. The mechanisms of action of AIT include the induction of very early desensitization of mast cells and basophils; generation of regulatory T and regulatory B (Breg) cell responses; regulation of IgE and IgG4; decreases in numbers and activity of eosinophils and mast cells in mucosal allergic tissues; and decreases in the activity of basophils in circulation. Skewing of allergen-specific effector T and effector B cells to a regulatory phenotype appears as a key event in the course of AIT and normal immune response to allergens. Recently, inducible IL-10–secreting Breg cells were also demonstrated to contribute to allergen tolerance through suppression of effector T cells and selective induction of IgG4 isotype antibodies. Allergen-specific regulatory T and Breg cells orchestrate a general immunoregulatory activity, which can be summarized as suppression of cytokines from inflammatory dendritic cells; suppression of effector TH1, TH2, and TH17 cells; suppression of allergen-specific IgE and induction of IgG4; and suppression of migration of mast cells, basophils, eosinophils, and effector T cells to tissues. A detailed knowledge of the mechanisms of AIT is not only important in designing the prevention and treatment of allergic diseases but might also find applications in the treatment of autoimmune diseases, organ transplantation, chronic infection, and cancer.